Relationship between crosslink density and physical properties of filled natural rubber vulcanizate / Norhasimah Abdul Hanan - Abdul Hanan, Norhasimah (Faculty of Applied Sciences, 2008)
This study is to find out which vulcanization system offer better vulcanizate properties with short vulcanization time. Relationship between crosslink density and physical properties of conventional vulcanizate system, efficient vulcanizate system, semiefficient vulcanizate system of SMR 10 rubber were determined. In this study rubber and other filler was masticated using two-raw mill machine at 70°C. Two-roll mill machine 18" in diameter with speed ratio 1:5:1 was used to sheet the compound and for incorporation of the vulcanizing ingredients. Tensile test, hardness test and density were determining relationship between crosslink density and physical properties of difference vulcanizate system. The swelling test was used to determine the crosslink density of vulcanizate system. In this study were found that conventional vulcanizate system give high value in crosslink density and corresponding to increased their physical properties such as tensile stress and density but increased their cure time.